The immediate effect of vaginal and caesarean delivery on anal sphincter measurements - Karcaaltincaba, Deniz (J Int Med Res, 2016)
OBJECTIVE: This study evaluated the effects of vaginal and caesarean delivery on internal and external anal sphincter muscle thickness using translabial ultrasonography (TL-US). METHODS: This prospective cohort study enrolled nulliparous women who either had vaginal or caesarean deliveries. The thickness of the hypoechoic internal anal sphincter (IAS) and hyperechoic external anal sphincter (EAS) at the 12, 3, 6, and 9 o’clock positions at the distal level were measured before delivery and within 24–48 h after delivery. RESULTS: A total 105 consecutive women were enrolled in the study: 60 in the vaginal delivery group and 45 in the caesarean delivery group. The IAS muscle thickness at the 12 o’clock position in the vaginal delivery group was significantly thicker before compared with after delivery (mean ± SD: 2.31 ± 0.74 mm versus 1.81 ± 0.64 mm, respectively). The EAS muscle thickness at the 12 o’clock position in the vaginal delivery group was significantly thicker before compared with after delivery (mean ± SD: 2.42 ± 0.64 mm versus 1.97 ± 0.85, respectively). CONCLUSIONS: There was significant muscle thinning of both the IAS and EAS at the 12 o’clock position after vaginal delivery, but not after caesarean delivery.